The art of taxidermy: Complementary course - Armiñana-García, Rafael (2023)
Taxidermy is an encounter between science, technique and art in favor of education and scientific culture. The objective of this research work is to propose a complementary course of basic taxidermy for the students of the second year of the Primary Teachers' career of the Pedagogical School "Manuel Ascunce Domenech", located in the city of Santa Clara, province of Villa Clara, Cuba. In order to carry out the research, the methods of information gathering and processing of the information gathered in their dialectic interrelation were used, within the latter, observation and survey stand out. It was found that in this institution there are no natural objects, namely animals preserved in liquid or dissected, which facilitate a better understanding when using them as a means of teaching the contents related to the teaching-learning process of Biology, and the students and teachers have insufficiencies related to the assembly of collections in liquid and the dissection of animals. In this sense, a program for the complementary course of basic taxidermy was elaborated and submitted to expert criteria for its evaluation. The implementation of this program made possible the assembly of different collections of animals by the students of the second year of the Primary Teachers' course of the Pedagogical School "Manuel Ascunce Domenech".